L-5-hydroxytryptophan promotes antitumor immunity by inhibiting PD-L1 inducible expression. Issue 6 (21st June 2022) - Huang, Jing; Wang, Xiaobo; Li, Bing; Shen, Shiyu; Wang, Ruina; Tao, Hongru; Hu, Junchi; Yu, Jin; Jiang, Hualiang; Chen, Kaixian; Luo, Cheng; Dang, Yongjun; et al.
Abstract : Background: The repression or downregulation of programmed death-ligand 1 (PD-L1) can release its inhibition of T cells and activate antitumor immune responses. Although PD-1 and PD-L1 antibodies are promising treatments for diverse tumor types, their inherent disadvantages and immune-related adverse events remain significant issues. The development of small molecule inhibitors targeting the interaction surface of PD-1 and PD-L1 has been reviving, yet many challenges remain. To address these issues, we aimed to find small molecules with durable efficacy and favorable biosafety that alter PD-L1 surface expression and can be developed into a promising alternative and complementary therapy for existing anti-PD-1/PD-L1 therapies. Methods: Cell-based screen of 200 metabolic molecules using a high-throughput flow cytometry assay of PD-L1 surface expression was conducted, and L-5-hydroxytryptophan (L-5-HTP) was found to suppress PD-L1 expression induced by interferon gamma (IFN-γ). Inhibition of PD-L1 induction and antitumor effect of L-5-HTP were evaluated in two syngeneic mouse tumor models. Flow cytometry was performed to investigate the change in the tumor microenvironment caused by L-5-HTP treatment. Results: We discovered that L-5-HTP suppressed IFN-γ-induced PD-L1 expression in tumor cells transcriptionally, and this effect was directly due to itself. Mechanistically, L-5-HTP inhibited IFN-γ-induced expression of RTK ligands and thus suppressed phosphorylation-mediated activation of RTK receptors and the downstream MEK/ERK/c-JUN signaling cascade, leading to decreased PD-L1 induction. In syngeneic mouse tumor models, treatment with 100 mg/kg L-5-HTP (intraperitoneal) inhibited PD-L1 expression and exhibited antitumor effect. L-5-HTP upregulated the ratio of granzyme B+ CD8+ activated cytotoxic T cells. An intact immune system and PD-L1 expression was critical for L-5-HTP to exert its antitumor effects. Furthermore, L-5-HTP acted synergistically with PD-1 antibody to improve anticancer effect. Conclusion: Our study illustrated L-5-HTP's inhibitory effect on PD-L1 induction stimulated by IFN-γ in tumor cells and also provided insight into repurposing L-5-HTP for use in tumor immunotherapy.